Literature Study: The Phenomenon Of Chemical Bonding's Misconceptions And Opportunities For Remediation - Nur Alawiyah; Resi Pratiwi (Departement of Mathematics Education, 2024)
This research aims to analyze the misconceptions that occur in chemical bonding materials and offer remediation processes. This type of research was library research with data taken from library materials or information. There were 32 scientific journals related to the research topic, then grouped within the last five years, and four scientific journals were produced that discussed misconceptions in chemical bonding material and four scientific journals that discussed the process of remediation of misconceptions in chemical bonding material. Based on the results of the review, misconceptions about chemistry occur in almost every sub-topic. The offer to remediate misconceptions that occur in this material is the ECIRR learning model, cognitive conflict strategy, and conceptual change strategy.